2021
DOI: 10.1371/journal.pone.0248774
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroids for impending late preterm (34-36+6 weeks) deliveries—A systematic review and meta-analysis of RCTs

Abstract: Background Administration of antenatal corticosteroids (ANC) for impending preterm delivery beyond 34 weeks of gestation continues to be a controversial issue despite various guidelines for obstetricians and gynaecologists. Objective To compare outcomes following exposure to ANC for infants born between 34–36+6 weeks’ gestation. Methods A systematic review of randomised controlled trials (RCT) reporting neonatal outcomes after ANC exposure between 34–36+6 weeks’ gestation using Cochrane methodology. Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
2
26
0
2
Order By: Relevance
“…Because of the administration of betamethasone, the rate of neonatal hypoglycemia in the study group was significantly increased, although this was expected (RR 1.60, 95% CI: 1.37 – 1.87) 43 . This was also confirmed in subsequent meta-analyses (RR 1.61, 95% CI: 1.38 – 1.87) 44 , 45 .…”
Section: Corticosteroids and Late Preterm Birth (> 34 Weeks Of Gestat...supporting
confidence: 72%
“…Because of the administration of betamethasone, the rate of neonatal hypoglycemia in the study group was significantly increased, although this was expected (RR 1.60, 95% CI: 1.37 – 1.87) 43 . This was also confirmed in subsequent meta-analyses (RR 1.61, 95% CI: 1.38 – 1.87) 44 , 45 .…”
Section: Corticosteroids and Late Preterm Birth (> 34 Weeks Of Gestat...supporting
confidence: 72%
“…A recent meta-analysis by Mangesh et al, which included seven RCTs, showed reduced need for respiratory support in the steroid category (relative risk 0.68), while neonatal hypoglycaemia risk was high. 3 Interestingly, the recent paper by Badreldin et al showed no respiratory benefit of ACS in late preterm deliveries. 4 Another high-risk group is neonates of type 1 and type 2 diabetic pregnant mothers, who have a 48% risk of hypoglycaemia.…”
Section: Dear Editormentioning
confidence: 98%
“…Different guidelines also differ widely (Table 1). In a recent metanalysis, Deshmukh and Patole 17 have summarized the evidence from 7 RCTs, n = 4,143 in the late preterm population. There was moderate quality of evidence of benefit in reducing the need for respiratory support.…”
Section: Evidence Of Use Of Antenatal Corticosteroids and Recommendation By Governing Bodiesmentioning
confidence: 99%
“…There was no data on long-term outcomes. 17 Considering the impact of hypoglycemia and no differences in outcomes related to RDS, surfactant, or admission, it is therefore better to restrict use of antenatal corticosteroids to cases where there is documented evidence of fetal lung immaturity by amniotic fluid analysis until further research.…”
Section: Evidence Of Use Of Antenatal Corticosteroids and Recommendation By Governing Bodiesmentioning
confidence: 99%